The Effect of Social Media Use Intensity on Anxiety, Depression and Stress Level During Covid-19 Pandemic Outbreak - Suhanda; Firda Firda Laela Najah; Yuliana Siti Nurazizah; Andry Agus Mulyana (Alta Dharma Publisher, 2021)
Background: The Covid-19 pandemic has had a significant impact on living things. Discussions about the issue of the coronavirus in Indonesia on social media have changed the behavior of social media users. Excessive use of social media will have the potential to cause mental health problems such as depression, anxiety, stress, risk of suicide, and impaired self-concept. Objective: This study aimed to determine the effect of social media on anxiety, depression, and stress during the pandemic. Method: This research used quantitative analytic analysis with a cross-sectional approach. A total of 200 people were selected by using random sampling. The research instrument used the intensity scale of social media use (SIPMS) and the Depression, Anxiety, Stress Scale (DASS 21) questionnaire. Result: The results showed that most respondents had a high intensity of social media use, as many as 118 respondents (59%). Conclusion: in conclusion that there was a significant relationship between the intensity of social media use and the level of anxiety, depression, and stress in adolescents in Sirnagalih Village, as evidenced by the results of Kendall's tau b = 0.000 statistical test < 0.05 and ranxiety=0.263, rdepression=0.257, and rstress=0.172